Acute effects of two warm-up strategies on the tennis serve speed of collegiate male tennis players - Uy, Dawn Albert Z. 1998- (College of Human Kinetics, University of the Philippines Diliman, 2019)
The purpose of the study is to determine the acute effects of two warm-up strategies: medicine ball warm-up and resistance band warm-up on the serve speed of tennis players. Ten(10) collegiate male tennis players participated in the study and performed three(3) warm-up protocols randomly and on non-consecutive days. The three warm-up protocols were dynamic stretching warm-up (control), medicine ball warm-up, and resistance band warm-up. Each warm-up session consisted of a three-minute jog, dynamic stretching exercises, respective warm-up protocol (medicine ball exercises or resistance exercises; no treatment for the control), five-minute moderate-intensity court warm-up, and a serve speed test. All three warm-up protocols were analyzed using repeated measures analysis of variance. Despite improvements in the average speed, no significant differences were found in all three warm protocols (p>0.05). This means that either of the three warm-up protocols is adequate enough to use as a warm-up strategy prior to a match.